Avaliação da atividade eletromiográfica dos músculos trapézio e eretor da espinha em pacientes portadores de desordens temporomandibulares antes e após o uso de placas oclusais - Strini, Paulinne Junqueira Silva Andresen (2008)
The human muscular system presents a set of structures acting in association and interacting between itself, reflecting clinically in the stomatognathic disorders and corporal position. In this work, had been evaluated the electromyographic activity of trapezius muscles, upper and middle part, in rest position, in scapula and head isometric extension, and lumbar part of longissimus and iliocostalis muscles, in the rest and in isometric extension of the trunk, bilaterally, as well as the abnormal head position (AHP) and postural alterations of skull and shoulders. Clinical and electromyographic examinations were done in 20 patients with Temporomandibular Disorders, before, one week and one month after myorelaxant occlusal splint instalation. The values of Root Mean Square (RMS) had been compared between itself for the Wilcoxon test (p<0,05). The results showed significant statistical differences between the right and left sides for longissimus and upper trapezius muscles, and between the stages of the research for the left iliocostalis, upper trapezius of both sides and right middle trapezius, as well as in the abnormal head position. Also had been observed reductions of the painfully symptom, maintenance of the rectification and alteration of the head inclination side. It can be concluded that exists an interrelation between the occlusion, the cervical and postural muscles, where any disequilibrium will be able to compromise distance muscular components and to harm the accomplishment of the organic functions, causing visible clinically alterations and intervening with the performance of the involved structures.